The Impact of CYP2D6 Genotyping on Tamoxifen Treatment - Roberta Ferraldeschi; William G. Newman (MDPI AG, 2010)
Tamoxifen remains a cornerstone of treatment for patients with oestrogen-receptor-positive breast cancer. Tamoxifen efficacy depends on the biotransformation, predominantly via the cytochrome P450 2D6 (CYP2D6) isoform, to the active metabolite endoxifen. Both genetic and environmental (drug-induced) factors may alter CYP2D6 enzyme activity directly affecting the concentrations of active tamoxifen metabolites. Several studies suggest that germline genetic variants in CYP2D6 influence the clinical outcomes of patients treated with adjuvant tamoxifen. Here, we review the existing data relating CYP2D6 genotypes to tamoxifen efficacy.